The case study in organizational management research: an introductory guide - Mendoza, Jorge (2016)
Research in organizational management faces the challenge of understanding, building and disseminating knowledge about a study object that presents itself as something subjective, difficult and complex to handle: the organizations or a group of them. In this situation, the case study as a research strategy of social phenomena is seen as a relevant option for the researcher, in a context in which the use of intensive over extensive strategies improves the quality of the understanding of this phenomenon in relation to the context in which it occurs. In this perspective, this paper seeks to provide a clearer view of the case study research on organizational management through a review of the literature on the subject and the authors’ own experience on this topic, so that questions about the use, opportunity and feasibility of this strategy will be answered.